Utilization of Augmented Reality in Conservation Folklore - Riezka Maghfirah; Naiza Ferona; M Fitra Waldi; Alfin Syatriawan; Arnawan Hasibuan (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
Folklore is a national cultural heritage that still has values ​​that should be developed and utilized for present and future life. Previously, folk tales were spread by word of mouth until finally the stories were known to many people, therefore folk tales were included in oral literature. In folklore there are many life messages that can be implemented in everyday life in order to become a better human being. However, it is a shame that folklore now sounds foreign to society, especially among children and teenagers. Seeing this problem, researchers offer a solution that can restore people's interest, especially teenagers and children, in folklore. By incorporating today's technology into folklore, it will help attract people's interest, especially teenagers and children, to return to reading folklore. Augmented Reality is a technology that can integrate computer objects, both two-dimensional and three-dimensional, into a real environment. This research uses a quantitative approach. Data collection was carried out through pretest and posttest in the form of multiple choice questions with four answer choices. Augmented reality can not only be a medium for increasing knowledge of folklore, but it can also be a medium for increasing students' sense of wanting to preserve folklore.